Raw Equid Milk: A Potential Risk for Q Fever? - Elisa Mazzotta; Alda Natale; Laura Bellinati; Letizia Ceglie; Laura Lucchese; Tahsin Onur Kevenk; Maria Luisa Menandro; Federica Giacometti; Leonardo Alberghini (Animals)
Equid milk (donkey or mare) has traditionally been consumed raw or fermented due to its distinctive chemical composition, which closely resembles human milk, and its nutritional benefits. Nowadays, interest in it is increasing, despite limited research on its microbiological risk. Coxiella burnetii (C. burnetii), a globally re-emerging zoonotic agent, has rarely been investigated in equid milk. The objective of this study was to demonstrate the applicability of selected analytical methods for detecting C. burnetii in raw equid milk. A commercial molecular assay was tested on three serial dilutions of one donkey milk sample contaminated with a C. burnetii plasmid, which showed no interference of donkey milk with real-time PCR detection. The commercial molecular assay and a serological assay routinely used in the laboratory were also applied to screen a total of 106 equid milks from 16 farms to assess their applicability to diagnostic samples. No C. burnetii DNA or anti-C. burnetii antibodies were detected in these screenings. In our study, the implemented methods appeared to be suitable for C. burnetii investigation in equid milk. While the overall low prevalence recorded in Italy among domestic species is reassuring, strategic surveillance and risk assessment remain essential considering the low infectious dose of C. burnetii and its zoonotic potential.